If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + 10 = 25 Reorder the terms: 10 + 11x = 25 Solving 10 + 11x = 25 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 11x = 25 + -10 Combine like terms: 10 + -10 = 0 0 + 11x = 25 + -10 11x = 25 + -10 Combine like terms: 25 + -10 = 15 11x = 15 Divide each side by '11'. x = 1.363636364 Simplifying x = 1.363636364
| 4*(x+2)=2x+3 | | 22.587/2.13 | | 2n-11=41 | | -7+3n=-28 | | 11x(9-7)= | | 3x=11x+30 | | 4x=-13.2 | | 60=-4(4x-3) | | 5*(x+3)=7 | | an=2-1/3^n | | 3r+22=46 | | 9+8b^2= | | 5*(x-2)=6 | | 24x^7-6x^3/6x^3 | | 4w^2+12w+9-25=0 | | x*2x+3=65 | | 15x-5y=20-10 | | 4w^2+4w+1-25=0 | | 63=10x-7 | | 15x-5y=20x+-10 | | 7q-18=3 | | (2x/3)-1 | | 2*2x-3=65 | | x^2-4x+4-49=0 | | 22x-x= | | 2*2x+3-65=0 | | (2+i)-(6-2i)= | | 2x^2+3-65=0 | | 43+x-19=36 | | 80+x-68=32 | | x^2-6x+-49=0 | | -2(4x-2-4)=5(x+2) |